Influence of weed management measures on glyphosate resistance and endophyte infection in naturalized Italian ryegrass (Lolium multiflorum). Issue 2 (10th May 2017) - Handayani, Valentina Dwi Suci; Tanno, Yuki; Yamashita, Masayuki; Tobina, Hiroyuki; Ichihara, Minoru; Ishida, Yoshiki; Sawada, Hitoshi
Abstract : Recently, glyphosate‐resistant Italian ryegrass ( Lolium multiflorum Lam.) was found on rice paddy levees in a western region of Shizuoka Prefecture, Japan. Naturalized populations of Italian ryegrass are frequently infected with fungal Epichloë endophytes. Endophytes often confer benefits to their host grasses. This study investigated the influence of five weed management treatments on glyphosate resistance and endophyte infection in Italian ryegrass that was growing on paddy levees where glyphosate‐resistant individuals were dominant. The weed management treatments were: (i) mowing once before the grass flowered; (ii) mowing once during flowering; (iii) mowing twice during flowering; (iv) glyphosate application before flowering; and (v) no treatment. The seeds were collected from the treatment plots in 2013 and 2014. The seeds were examined for endophyte infection and the seedlings that had been grown from the seeds were tested for the frequency of glyphosate resistance. The seedlings that had been derived from the glyphosate treatment showed higher frequencies of glyphosate resistance than those seedlings that had been derived from all the other treatments. Endophytes were found in all populations of the seeds from the paddy levees, with higher infection rates in the seeds that had been derived from the glyphosate treatment and the twice‐mowed treatment. There was a significant relationship between the endophyte infection frequency in the seeds and glyphosate resistance in the seedlings that had been grown from the same populations. The results indicate that where glyphosate herbicides are frequently used, selection for glyphosate‐resistant Italian ryegrass occurs, and along with this, the frequency of endophyte infection also increases.